Analisis Sistem Pembumian untuk Mengamankan Instalasi Listrik di Program Studi Teknik Elektro Fakultas Teknik Universitas Udayana Jimbaran Bali - setyawan, kadek rudi andika; Janardana, I Gusti Ngurah; Utama, Ngakan Putu Satriya (Majalah Ilmiah Teknologi Elektro, 2018)
Each building's electrical panel must be connected to grounding system, so that the installation of electricity, equipment and humans residing in the building will be protected from the danger of current or over voltage. This research was conducted to determine the characteristics of the grounding system (single rod, multiple rod s?L and s?L, grid and plate) with the resistance value ? 5 Ohm [2], which can be securing electrical installation in Electrical Engineering Department of Udayana University, this research will be complited using metode based by : Collecting data of resistance soil type (?) at the location of Electrical Engineering Department Faculty of Engineering in Udayana University, calculating the grounding resistance based on data of soil resistance type (?), analyze the characteristics of earthing system with resistance soil type (?) according to the requirement of R ? 5 ? with single rod method, multiple rod s <L and s> L, plate and grid. Based on the research that has been done, rho (?) in the area of Electrical Engineering Department is 256,224 ?-meters. The results of the analysis to obtain the value of R ? 5 ? in get a single rod grounding system, with L = 82 meters, Rsr = 4.98 ?. The multiple rod type s?L, with L = 42 and s = 40 meters, RM = 4.90 ?, while the multiple rod type> L, with L = 42 and s = 43 meters, Rm = 4.98 ?. Type plate with 2x1 meter plate size, in parallel of 10 pieces and t = 4 meters big Rp = 4,56 ? and type of grid with h = 3 meters, L = 1189 meters, big RG 4,79 ?. The grounding system that is possible to install is a grouding type systems plate or grid, since its planting is shallower than the single rod grouding system type, multiple rods s?L and s> L since the limestone ground texture.